(untitled) (Bioagro, 2024)
Shading nets are used to reduce the amount of radiant energy reaching crops. The objective of the work was to compare the influence of black and red shading nets on the production of nine American lettuce cultivars in the Autumn period under the conditions of the Central Department of Paraguay. The experiment was carried out in the Experimental Field of the Departmental Agronomic Center (CAD) in the Municipality of Julián Augusto Saldívar. The treatments consisted of the combination of two types of shading netting (red with 35% shade and black with 35% shade) and nine cultivars of American lettuce (Julia, Dora, Angelina, Tainá, Sun Valley, Betty, Lucy Brown, Mara, and Serena) totaling 18 treatments. The experiment consisted in a complete randomized block design, arranged in split blocks 2×9 (the color of shading netting was considered the main plot, and the lettuce cultivars as the secondary plot) with four repetitions. Each experimental unit consisted of four crop rows with seven plants. Plant diameter, plant height, head diameter and height, commercial number of leaves per plant, fresh mass, and commercial productivity were evaluated. The data were subjected to analysis of variance, and when differences were found, the means were compared by the Scott-Knott test at 5% probability. The results indicate that using the red netting with the Serena and Dora cultivars provides greater fresh mass and commercial production.